Minimum Problem

Calculus Level 4

Find the three points on the curve y = x 2 + 1 x 2 1 y=\displaystyle{\frac{x^2+1}{x^2-1}} which have the shortest distances to the point P ( 0 , 1 ) P(0,1) . If the x x -coordinates of these points are x 1 x_1 , x 2 x_2 , and x 3 x_3 , where x 1 < x 2 < x 3 x_1<x_2<x_3 , find ( 3 x 1 + 6 x 2 + 9 x 3 ) 2 (3x_1+6x_2+9x_3)^2 .


The answer is 108.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Since y y is an even function, it is symmetrical on the y y -axis. It has two asymptotes at x = ± 1 x=\pm 1 . The shortest distances are the normals from the three parts of the curve y y that passes through P ( 0 , 1 ) P(0,1) . Let the gradient of a line passing through P ( 0 , 1 ) P(0,1) be m = y 1 x m= \dfrac {y-1}x . Then, the normal will also have a gradient of m m . Let us find the gradient of a point ( x , y ) (x,y) of the curve.

y = x 2 + 1 x 2 1 ( x 2 1 ) y = x 2 + 1 Differentiating both sides w.r.t x 2 x y + ( x 2 1 ) d y d x = 2 x ( x 2 1 ) d y d x = 2 x ( 1 y ) = 2 x ( 1 x 2 + 1 x 2 1 ) = 4 x x 2 1 d y d x = 4 x ( x 2 1 ) 2 Note that d y d x = 1 m 4 x ( x 2 1 ) 2 = x y 1 4 x ( y 1 ) x ( x 2 1 ) 2 = 0 8 x x 2 1 x ( x 2 1 ) 2 = 0 8 x x ( x 2 1 ) 3 = 0 x ( 8 ( x 2 1 ) 3 ) = 0 \begin{aligned} y & = \frac {x^2+1}{x^2-1} \\ (x^2-1)y & = x^2+1 & \small \color{#3D99F6} \text{Differentiating both sides w.r.t }x \\ 2xy +(x^2-1)\frac {dy}{dx} & = 2x \\ (x^2-1)\frac {dy}{dx} & = 2x(1-y) \\ & = 2x \left(1- \frac {x^2+1}{x^2-1}\right) \\ & = \frac {-4x}{x^2-1} \\ \frac {dy}{dx} & = \frac {-4x}{(x^2-1)^2} & \small \color{#3D99F6} \text{Note that } \frac {dy}{dx} = - \frac 1m \\ \implies \frac {-4x}{(x^2-1)^2} & = - \frac x{y-1} \\ 4x(y-1) - x(x^2-1)^2 & = 0 \\ \frac {8x}{x^2-1} - x(x^2-1)^2 & = 0 \\ 8x - x(x^2-1)^3 & = 0 \\ x \left(8-(x^2-1)^3 \right) & = 0 \end{aligned}

x = { x = 0 ( x 2 1 ) 3 = 8 x = ± 3 \implies x = \begin{cases} x = 0 \\ (x^2-1)^3 = 8 & \implies x = \pm \sqrt 3 \end{cases}

( 3 x 1 + 6 x 2 + 9 x 3 ) 2 = ( 3 3 + 6 ( 0 ) + 9 3 ) 2 = 108 \implies \left(3x_1 + 6x_2 + 9x_3\right)^2 = \left(-3\sqrt 3 + 6(0) + 9\sqrt 3\right)^2 = \boxed{108}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...